Preparation method and application of organic-inorganic artificial composite solid electrolyte interface layer

By using the organic-inorganic artificial composite solid electrolyte interface layer in negative electrode-free lithium metal batteries, the nucleation barrier of lithium ions is regulated, the problem of poor cycle stability of the battery is solved, and the cycle stability and efficiency are achieved, and there is a wide range of commercial application potential.

CN119581564AInactive Publication Date: 2025-03-07KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411764098.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are significant challenges in the cycle stability of negative electrode lithium metal batteries, mainly because there is no additional excess lithium in negative electrode lithium metal batteries to compensate for the irreversible lithium loss, resulting in uneven deposition of lithium and a rapidly growing solid electrolyte interface layer, thereby shortening the cycle life of the battery.

Method used

The organic-inorganic artificial composite solid electrolyte interface layer is adopted to reduce the nucleation barrier of lithium ions on the copper surface by precise interface regulation of the copper current collector, and promote uniform deposition of lithium, thereby improving the cycling stability and efficiency of the battery.

Benefits of technology

It significantly improves the cycle stability and efficiency of negative electrode-free lithium metal batteries, demonstrates long cycle stability, good rate performance and significant safety performance improvement, and has broad commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168433610000081
    Figure BDA0005168433610000081
  • Figure BDA0005168433610000091
    Figure BDA0005168433610000091
  • Figure HDA0005168433730000011
    Figure HDA0005168433730000011
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an organic-inorganic artificial composite solid electrolyte interface layer, and belongs to the technical field of lithium metal batteries. The organic polymer, the black phosphorene, the conductive carbon black and other inorganic substances are uniformly mixed to construct the organic-inorganic artificial composite interface layer, and the organic-inorganic artificial composite interface layer can induce uniform lithium deposition, reduce the local current density caused by nonuniformity and roughness of the surface of the copper current collector, reduce the lithium nucleation barrier, and improve the lithium ion battery performance. Meanwhile, the affinity of deposited lithium and a current collector is enhanced, the interface impedance of the negative-electrode-free lithium metal battery is remarkably reduced, and the lithium dendrite growth of a lithium metal negative electrode is inhibited; the cathode-free lithium metal battery assembled by adopting the copper current collector modified by the organic-inorganic artificial composite interface layer shows long cycle stability, good rate capability and remarkable safety performance, and has a wide commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage batteries, and in particular to a preparation method and application of an organic-inorganic artificial composite solid electrolyte interface layer for the interface stability of a negative electrode of a negative electrode-free lithium metal battery. Background Art

[0002] In recent years, with the rapid development of electric vehicles and portable electronic devices, the demand for high energy density rechargeable batteries has increased significantly. Lithium (Li) metal has a high theoretical specific capacity (3860 mAh g -1 ) and low redox potential (-3.04Vvs SHE) are widely regarded as ideal negative electrode materials. Lithium metal-based batteries (LMBs) with lithium metal as the negative electrode have once again attracted widespread attention from researchers as the next generation of advanced energy storage technology. Among them, anode-free lithium metal batteries (AFLMBs) are considered to be an ideal choice for future battery technology. AFLMB does not use any anode active materials in the battery manufacturing process, making it possible to achieve an energy density of more than 400Whkg-1. In addition to its excellent energy density, AFLMB also has many advantages, such as simplified manufacturing process and low production cost. In addition, the manufacturing infrastructure of AFLMB is highly compatible with existing lithium-ion batteries, which makes it feasible for practical applications. However, the current poor cycling stability of AFLMB has seriously hindered its large-scale application. Therefore, in-depth research on the cycling stability of AFLMB will be an important direction to promote its commercialization.

[0003] Anode-free lithium metal batteries (AFLMBs) present significant challenges in terms of cycle stability, mainly because there is no additional excess lithium in anode-free lithium metal batteries to compensate for the irreversible lithium loss. In the initial stage, the lithium metal deposited on the copper current collector exhibits a high overpotential, resulting in an unstable and uneven solid electrolyte interface layer formed on the anode, which cannot effectively protect the deposited lithium. This situation triggers the rapid growth of the solid electrolyte interface layer and poor Coulombic efficiency (CE), which in turn shortens the cycle life of the entire battery. To solve this problem, designing an artificial solid electrolyte interface layer on the current collector has been proposed as an effective strategy. The artificial solid electrolyte interface layer can induce uniform lithium deposition, reduce the local current density caused by the uneven and rough surface of the current collector, and reduce the lithium nucleation barrier. At the same time, the artificial solid electrolyte interface layer also enhances the affinity between the deposited lithium and the current collector, avoids direct contact between the deposited lithium and the electrolyte, effectively inhibits side reactions and stabilizes the interface. However, there is no artificial solid electrolyte interface layer with excellent performance. Summary of the invention

[0004] The present invention provides a method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, which can improve the stability of the negative electrode interface layer of the negative electrode-free lithium metal battery. The interface layer is applied to the negative electrode-free lithium metal battery, and through precise interface regulation of the copper current collector, the nucleation barrier of lithium ions on the copper surface is effectively reduced, and the uniform deposition of lithium is promoted, thereby improving the cycle stability and efficiency of the battery.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0007] The organic component was dissolved in N-methylpyrrolidone, and the inorganic component was added. The mixed slurry was placed in an area of ​​10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100°C, and keep it warm for 16h to 20h to obtain an artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-Polymer) on the Cu foil.

[0008] The organic components include polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyglycidyl methacrylate (PGMA), polyhydroxyethyl methacrylate (PHEMA), polytrifluoroethyl methacrylate (PTFEMA); polydioxolane (PDOL), polyacrylonitrile (PAN), polyurethane (TPU), etc. The organic components can be monomers of various organic substances (glycidyl methacrylate, hydroxyethyl methacrylate, trifluoroethyl methacrylate, dioxolane) or high molecular weight polymers (polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyurethane) that have been polymerized on the market, and N-methylpyrrolidone is added to polymerize the monomers or dissolve the high molecular weight polymers. The ratio of the total amount of monomers or the high molecular weight polymer to N-methylpyrrolidone is 10wt% to 90wt%: 10wt% to 90wt%.

[0009] The inorganic component is a mixture of black phosphorene and conductive carbon black (Super P) in any proportion.

[0010] The mass ratio of the organic component to the inorganic component is 1-9:9-1.

[0011] The present invention also provides the use of the organic-inorganic artificial composite solid electrolyte interface layer prepared by the preparation method to improve the interface stability of the negative electrode-free lithium metal battery in the preparation of the negative electrode-free lithium metal battery, and the negative electrode-free lithium metal battery is prepared using the Cu current collector, positive electrode sheet, diaphragm and electrolyte of the artificial composite solid electrolyte interface layer.

[0012] The positive electrode sheet includes one or more of a lithium iron phosphate positive electrode sheet, a lithium cobalt oxide positive electrode sheet, a nickel cobalt manganese oxide 811 positive electrode sheet, a nickel cobalt manganese oxide 622 positive electrode sheet, and a nickel cobalt manganese oxide 523 positive electrode sheet; the diameter of the positive electrode sheet is preferably 10 to 12 mm.

[0013] The diaphragm is any one of a polypropylene film PP, a polyethylene film PE, and a PP / PE composite film, and its diameter is preferably 18 to 20 mm.

[0014] The electrolyte is one or more of 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%, 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with 5%FEC, 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with 5%VC, and 1M LiPF6in DEC:DMC:EC=1:1:1Vol%with 5%VEC.

[0015] Beneficial effects of the present invention:

[0016] The organic-inorganic artificial composite solid electrolyte interface layer of the present invention can improve the stability of the negative electrode interface layer of a negative electrode-free lithium metal battery. The interface layer is applied to a negative electrode-free lithium metal battery. Through precise interface regulation of the copper current collector, the nucleation barrier of lithium ions on the copper surface is effectively reduced, and the uniform deposition of lithium is promoted, thereby improving the cycle stability and efficiency of the battery, demonstrating long cycle stability, good rate performance and significantly improved safety performance, and has broad commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Comparison of the capacity retention rates of Example 2 and Comparative Example 1;

[0018] Figure 2 Comparison of the first-cycle lithium ion nucleation overpotentials of Example 2 and Comparative Example 1. DETAILED DESCRIPTION

[0019] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0020] The positive electrode sheet used in the embodiment includes one or more of a lithium iron phosphate positive electrode sheet, a lithium cobalt oxide positive electrode sheet, a nickel cobalt manganese oxide 811 positive electrode sheet, a nickel cobalt manganese oxide 622 positive electrode sheet, and a nickel cobalt manganese oxide 523 positive electrode sheet; the diameter of the positive electrode sheet is preferably 10 to 12 mm; it can be a conventional commercially available positive electrode sheet, or it can be prepared by itself according to conventional methods.

[0021] The electrolyte used in the embodiment is a conventional electrolyte, including one or more of 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%, 1MLiPF6 in DEC:DMC:EC=1:1:1Vol%with 5%FEC, 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with5%VC, and 1M LiPF6 in DEC:DMC:EC=1:1:1Vol%with 5%VEC, all of which are commercially available conventional products.

[0022] The diaphragm used in the embodiment is any one of polypropylene film PP, polyethylene film PE, and PP / PE composite film, all of which are conventional commercial products, and the diameter thereof is preferably 18 to 20 mm.

[0023] The organic component used in the examples can be a conventional commercially available polymer or a polymer prepared from polymer monomers by conventional methods.

[0024] Example 1

[0025] Preparation of 811 positive electrode sheet:

[0026] The polycrystalline small particles of lithium nickel cobalt manganese oxide, conductive carbon black (Super P), and dispersant (PVDF) were mixed with N-methylpyrrolidone (NMP) solvent in a mass ratio of 8:1:1 to form a slurry. The slurry was then coated on a 15 μm thick aluminum foil with a coating thickness of 50 μm to 150 μm. After drying at 80 °C in a vacuum oven for 12 hours, the coating was rolled and punched to obtain a mass loading of 1.8 to 2.5 mg / cm 2 Nickel cobalt manganese oxide 811 positive electrode sheet.

[0027] Example 2

[0028] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0029] The organic polymer component polyethylene oxide (PEO) was dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to PEO was 2.45 g:0.05 g), and a mixture of inorganic components black phosphorene and Superp (the mass ratio of black phosphorene to Superp was 0.1 g:0.1 g) was added, and the mixture was ground and mixed evenly. The mixed slurry was placed on a 10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, and dry it for 16h to obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PEO) on the Cu foil. The obtained current collector is the BP&SP-PEO@Cu current collector.

[0030] Full battery assembly: The assembly was carried out in an argon-protected glove box, wherein the positive electrode used the nickel cobalt manganese oxide 811 positive electrode sheet prepared as described above, the negative electrode current collector used the BP&SP-PEO@Cu current collector (diameter 10-12 mm), the electrolyte used 1MLiPF6in DEC:DMC:EC=1:1:1Vol%with 5%FEC, and the diaphragm used was a 2400PP diaphragm.

[0031] Li||Cu battery assembly: The assembly was carried out in an argon-protected glove box, where the electrolyte used 1M LiPF6 inDEC:DMC:EC=1:1:1Vol%with 5%FEC, the positive electrode used BP&SP-PEO@Cu (diameter 10~12mm), the negative electrode used lithium sheet, and the separator used 2400PP / PE separator.

[0032] Full battery test: The assembled full battery is charged and discharged at a constant current at 30°C. First, it is allowed to stand for 16 hours to ensure that the electrolyte is fully infiltrated on the electrode surface. Then, the charge and discharge test is performed with a voltage range of 2.7V to 4.3V and a rate of 1C. The capacity retention rate is recorded after 200 cycles. The full battery that has been cycled 200 times is tested for AC impedance spectroscopy (EIS) using Shanghai Chenhua electrochemical analyzer to record its impedance value.

[0033] Comparison of nucleation overpotentials of Li||Cu batteries: The assembled Li||Cu batteries were charged and discharged at constant current at 30°C. First, they were left to stand for 12 hours to ensure that the electrolyte was fully infiltrated on the electrode surface. Then, charge and discharge tests were performed. First, they were discharged at a current density of 1 mA for 1 hour, and then charged at a current density of 1 mA to a cutoff voltage of 1 V for 1 cycle to record their nucleation overpotential.

[0034] Example 3

[0035] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0036] The organic polymer component polyvinylidene fluoride (PVDF) was dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to PVDF was 2.375 g:0.125 g), and the inorganic component black phosphorene and Superp mixture (the mass ratio of black phosphorene to Superp was 0.1 g:0.1 g) was added and ground and mixed evenly. The mixed slurry was placed in an area of ​​10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 20h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PVDF) on the Cu foil. The obtained current collector is BP&SP-PVDF@Cu current collector.

[0037] The battery was assembled and tested in the same manner as in Example 2.

[0038] Example 4

[0039] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0040] The organic polymer component glycidyl methacrylate (GMA) monomer was dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to GMA monomer was 2g:0.5g), 0.001g of azobisisobutyronitrile was added, and polymerized at 80°C for 1h to obtain polyglycidyl methacrylate (PGMA). The obtained organic polymer component PGMA and the mixture of inorganic components black phosphorene and Super p (the mass ratio of black phosphorene to Super p was 0.2g:0.1g) were ground and mixed evenly, and the mixed slurry was placed on an area of ​​10×10cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 18h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PGMA) on the Cu foil. The obtained current collector is the BP&SP-PGMA@Cu current collector.

[0041] The battery was assembled and tested in the same manner as in Example 2.

[0042] Example 5

[0043] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0044] The hydroxyethyl methacrylate (HEMA) monomer and N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to HEMA monomer is 1.9 g:0.6 g) are uniformly mixed, 0.001 g of azobisisobutyronitrile is added, and polymerized at 80°C for 1 h to obtain poly(hydroxyethyl methacrylate) (PHEMA), and the obtained organic polymer component and the mixture of inorganic components black phosphorene and Super p (the mass ratio of black phosphorene to Super p is 0.25 g:0.05 g) are ground and mixed uniformly, and the mixed slurry is placed on an area of ​​10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 18h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PHEMA) on the Cu foil. The obtained current collector is the BP&SP-PHEMA@Cu current collector.

[0045] The battery was assembled and tested in the same manner as in Example 2.

[0046] Example 6

[0047] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0048] The trifluoroethyl methacrylate (TFEMA) monomer and N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to FEMA monomer is 1.8g:0.7g) are uniformly mixed, 0.001g of azobisisobutyronitrile is added, and polymerized at 80°C for 1h to obtain poly(trifluoroethyl methacrylate) (PTFEMA), and the obtained organic polymer component and the mixture of inorganic components black phosphorene and Super p (the mass ratio of black phosphorene to Super p is 0.1g:0.1g) are ground and mixed uniformly, and the mixed slurry is placed on an area of ​​10×10cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 18h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PTFEMA) on the Cu foil. The obtained current collector is the BP&SP-PTFEMA@Cu current collector.

[0049] The battery was assembled and tested in the same manner as in Example 2.

[0050] Example 7

[0051] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0052] The dioxolane (DOL) monomer and N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to DOL monomer is 1.5g:1g) are uniformly mixed, 0.001g of lithium hexafluorophosphate (LiPF6) is added, and polymerization is carried out at room temperature for 6h to obtain polydioxolane (PDOL). The obtained organic polymer component and the mixture of inorganic components black phosphorene and Super p (the mass ratio of black phosphorene to Super p is 0.2g:0.1g) are ground and mixed uniformly, and the mixed slurry is placed on an area of ​​10×10cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 16h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PDOL) on the Cu foil. The obtained current collector is the BP&SP-PDOL@Cu current collector.

[0053] The battery was assembled and tested in the same manner as in Example 2.

[0054] Example 8

[0055] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0056] The organic polymer component polyacrylonitrile (PAN) was dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to PAN was 2 g:0.5 g), and a mixture of inorganic components black phosphorene and Superp (the mass ratio of black phosphorene to Superp was 0.15 g:0.1 g) was added and ground and mixed evenly. The mixed slurry was placed on a 10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 16h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-PAN) on the Cu foil. The obtained current collector is BP&SP-PAN@Cu current collector.

[0057] The battery was assembled and tested in the same manner as in Example 2.

[0058] Example 9

[0059] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0060] The organic polymer component polyurethane (TPU) was dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to PAN was 2 g:0.5 g), and the inorganic component black phosphorene and Superp mixture (the mass ratio of black phosphorene to Super p was 0.2 g:0.1 g) was added and ground and mixed evenly. The mixed slurry was placed on an area of ​​10×10 cm -2 , on a Cu foil with a thickness of 9um, use a scraper applicator with a height of 30um to evenly spread the mixed slurry on the Cu foil, place it in a vacuum drying oven at a temperature of 100℃, dry it for 16h, and obtain a 15um thick artificial composite organic-inorganic solid electrolyte interface layer (BP&SP-TPU) on the Cu foil. The obtained current collector is the BP&SP-TPU@Cu current collector.

[0061] The battery was assembled and tested in the same manner as in Example 2.

[0062] Example 10

[0063] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0064] Hydroxyethyl methacrylate (HEMA) monomer, trifluoroethyl methacrylate (TFEMA) monomer, glycidyl methacrylate (GMA) monomer and N-methyl pyrrolidone (the mass ratio of N-methyl pyrrolidone to hydroxyethyl methacrylate (HEMA) monomer, trifluoroethyl methacrylate (TFEMA) monomer and glycidyl methacrylate (GMA) monomer is 1.9g:0.2g:0.2g:0.2g), 0.001g of azobisisobutyronitrile is added, and polymerization is carried out at 80°C for 1h to obtain polyhydroxyethyl methacrylate-glycidyl methacrylate-trifluoroethyl methacrylate block organic polymer (PHGT), and the obtained organic polymer component and the inorganic component black phosphorene and Super p (black phosphorene and Super p) are prepared. The mixed slurry was evenly cast on Cu foil using a scraper coater with a height of 30 um and placed in a vacuum drying oven at a temperature of 100°C for 20 h to obtain an artificial composite solid electrolyte interface layer (BP&SP-PHGT) with a thickness of about 15 um on the Cu foil. The obtained current collector is the BP&SP-PHGT@Cu current collector.

[0065] The battery was assembled and tested in the same manner as in Example 2.

[0066] Embodiment 11

[0067] A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer for improving the interface stability of a negative electrode-free lithium metal battery, the specific steps are as follows:

[0068] Polyethylene oxide (PEO) and polyvinylidene fluoride (PVDF) precursor solution dissolved in N-methylpyrrolidone (the mass ratio of N-methylpyrrolidone to PEO and PVDF is 2g:0.25g:0.25g) and a mixture of inorganic components black phosphorene and Super p (the mass ratio of black phosphorene to Super p is 0.2g:0.1g) are ground and mixed evenly, and the mixed slurry is evenly cast on Cu foil using a scraper coater with a height of 30um, placed in a vacuum drying oven at a temperature of 100℃, and dried for 18h to obtain an artificial composite solid electrolyte interface layer (BP&SP-PEV) with a thickness of about 15um on the Cu foil. The obtained current collector is the BP&SP-PEV@Cu current collector.

[0069] The battery was assembled and tested in the same manner as in Example 2.

[0070] Comparative Example 1

[0071] A battery was assembled using Cu foil without an artificial composite interface layer and tested according to the method of Example 2.

[0072] Figure 1 The figure shows the capacity retention rate comparison between Example 2 and Comparative Example 1. It can be seen from the figure that the Cu foil with an artificial composite interface layer can significantly improve the cycle stability of the battery, delay the battery capacity decay, and improve the battery performance.

[0073] Figure 2 This is a comparison of the first-cycle lithium ion nucleation overpotentials of Example 2 and Comparative Example 1. It can be seen from the figure that the Cu foil with an artificial composite interface layer can reduce the nucleation barrier of lithium ions, showing a lower nucleation overpotential, more uniform lithium deposition, and reduced lithium dendrite formation.

[0074] In order to ensure that the data are more comparable, the above-mentioned embodiments and comparative examples all use the same positive electrode material, separator, and electrolyte to prepare batteries. The test results of the batteries assembled by Examples 2-11 and Comparative Example 1 are shown in Tables 1, 2, and 3 below. It can be seen from Tables 1 to 3 that the artificial composite organic-inorganic solid electrolyte interface layer prepared in the embodiments of the present invention can significantly improve the cycle stability and coulombic efficiency of the battery, while reducing the nucleation overpotential of lithium ions on the copper current collector, thereby improving the battery performance.

[0075] Table 1

[0076] Battery serial number Full battery 200 cycle capacity retention rate Example 2 81.85% Example 3 78.15% Example 4 79.10% Example 5 75.56% Example 6 76.31% Example 7 74.15% Example 8 79.21% Example 9 78.56% Example 10 76.50% Embodiment 11 77.15% Comparative Example 1 0%

[0077] Table 2

[0078]

[0079]

[0080] Table 3

[0081] Battery serial number Li||Cu battery lithium ion first nucleation overpotential Example 2 -71mV Example 3 -88mV Example 4 -89mV Example 5 -84mV Example 6 -86mV Example 7 -93mV Example 8 -92mV Example 9 -87mV Example 10 -80mV Embodiment 11 -89mV Comparative Example 1 -161mV

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an organic-inorganic artificial composite solid electrolyte interface layer, characterized in that: The specific steps are as follows: The organic component is dissolved in N-methylpyrrolidone, and the inorganic component is added. The mixed slurry is evenly applied on the Cu foil and placed in a vacuum heat preservation at 100° C. for 16 h to 20 h to obtain an artificial composite organic-inorganic solid electrolyte interface layer on the Cu foil.

2. The method for preparing the organic-inorganic artificial composite solid electrolyte interface layer according to claim 1, characterized in that: The organic component includes one of polyethylene oxide, polyvinylidene fluoride, polyglycidyl methacrylate, polyhydroxyethyl methacrylate, polytrifluoroethyl methacrylate, polydioxolane, polyacrylonitrile and polyurethane.

3. The method for preparing the organic-inorganic artificial composite solid electrolyte interface layer according to claim 1, characterized in that: The inorganic component is a mixture of black phosphorene and conductive carbon black in any proportion.

4. The method for preparing the organic-inorganic artificial composite solid electrolyte interface layer according to claim 1, characterized in that: The mass ratio of the organic component to the inorganic component is 1-9:9-1.

5. Use of the organic-inorganic artificial composite solid electrolyte interface layer prepared by the preparation method of claim 1 in the preparation of a negative electrode-free lithium metal battery.

Citation Information

Patent Citations

  • Negative plate, preparation method thereof and lithium battery

    CN107482224A

  • Current collector, preparation method and application thereof

    CN112259741A

  • Lithium-free negative electrode, preparation method thereof and lithium-sulfur battery

    CN118039784A

Cited By

  • High-dielectric / solvophobic synergistic artificial interface protection layer as well as preparation method and application thereof

    CN121709618A

  • High dielectric / solvent repellent synergistic artificial interface protective layer, and preparation method and application thereof

    CN121709618B